Pelaksanaan Edukasi Safety Touch Dalam Mengatasi Pelecehan Seksual Pada Anak - Khadijah; Hendra; Ade S. Anhar (STAI AL-AMIN, 2025)
Child sexual abuse is a serious problem that can adversely affect the psychological and social development of children. Education about safety touch at PAUD Al Amanah Parado is expected to provide early understanding to children about the importance of maintaining body boundaries and protecting themselves from unwanted touches. Data collection techniques used include observation, in-depth interviews, and documentation. Data sources consisted of teachers, parents, and children at PAUD Al Amanah Parado. The research procedure was carried out by observing safety touch education activities, interviewing teachers and parents regarding perceptions and program implementation, collecting supporting documents relevant to the implementation of activities. Data analysis techniques were carried out by means of qualitative analysis in which data obtained from interviews and observations were analyzed to find patterns, themes, and related meanings. The results showed that after safety touch education was conducted, the knowledge and understanding of students increased from the aspects of understanding personal body, distinguishing touch, courage to speak, as well as teacher and parent involvement. In its implementation, various forms of activities have been carried out including role playing, the use of interactive images and posters, storytelling, hands-on simulations, and collaboration with parents, this has also had a positive impact on children in understanding their body boundaries.